Competence training as a driver of competitive advantages for students in higher education - Belchior-Rocha, H.; Casquilho-Martins, I.; Almeida, F.; Simões, E. (9th World Conference on Learning, Teaching and Educational Leadership, 2018)
Abstract id: 29498